Sengketa Ekonomi Syariah Dan Solusi Penyelesaiannya - Nandang Ihwanudin (ISLAMICA, 2016)
The rapid growth of the banking and Islamic financial institutions did not ensure that will be a lot of sharia economic disputes brought to the Religious Court. The number of resolution options of dispute sharia economy (choice of forum) is often cited as the cause since besides through litigation (litigation effort) in a religious court, sharia economic disputes can also be resolved by non-litigation (non-litigation effort), for example by mediation or through Arbitration Service. But now, a special dispute resolution options such as Islamic banking has been eliminated and can only be resolved by the Court of religion by the Constitutional Court Decision No. 93 / PUU-X / 2012 dated August 29, 2013. This writing will be more focused on the philosophical study of sharia economic disputes and completion. Results of the analysis is that the sharia economic disputes are civil disputes which subject and object of the law based on sharia. The occurrence of a dispute can be caused by two things, namely breach of contract and tort. The solution can be done through two ways, namely litigation on Basyarnas and in addition to Islamic banking disputes and Religious Courts as the absolute authority (article 49 UUPA).